Managing a Sustainable and Low-Carbon Society (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Modern society faces various global and regional challenges, including climate change and sustainable development. In order to deal with these challenges, society must be managed properly to follow a sustainable and low-carbon pathway. To advance the studies on this topic, 13 articles have been included in a Special Issue of the “International Journal of Environmental Research and Public Health”. This is a reprint of the 13 articles published in the Special Issue. The themes covered by the 13 articles include the driving forces of carbon emissions, the carbon market, implications of regional and global low-carbon pathways, green finance, green growth, and air pollution. Various methods have been used in these studies, such as computable general equilibrium (CGE) models, econometric models, and machine learning methods. Most of the articles provide new insights based on evidence from China while the others focus on several regions and the global economy.